The Implementation of Village Boundaries at Halmahera Selatan Regency Maluku Utara Province: A Study of the Implementation of Regional Regulation 07/2016 - Anas, Djoan Dano; Sjamsuddin, Sjamsiar; Saleh, Choirul; Haryono, Bambang Santoso (IJOSMAS, 2023)
Implementation is part of the public policy cycle due to political decisions in an organization. Implementation describes the intention and objective of government policy to the public. The success rate of policy implementation depends on the implementer. The regime change from New Order to Reformation Era allows the government to establish a new administrative area. In addition, regional autonomy policies change due to regional demands and a strong influence of culture and customs. Regional expansion paid attention to the principles of autonomous boundaries and community welfare of the new administration area. Regional expansion refers to the geography, community, efficiency, managerial, technique, and social principles. Furthermore, regional expansion incorporated culture and customs due to differing cultures inside a region, encouraging the community to govern their region within the framework of the Republic of Indonesia. Maluku Utara is one of the Indonesian provinces that separated from Maluku Province. The Government established Maluku Utara as a new province as a response. Halmahera Selatan is one of the regencies in the Maluku Utara province, which possesses a strong influence on Bacan Sultanate culture and customs. In addition, Halmahera Selatan has a low development rate compared to other regions, except for human resources and infrastructure.